2010
DOI: 10.1308/147870810x476746
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent acute pancreatitis as the first and sole presentation of undiagnosed primary hyperparathyroidism

Abstract: Introduction We highlight the pitfalls in delaying the diagnosis of primary hyperparathyroidism (pHPT) in patients with acute pancreatitis as the sole clinical presentation. Primary hyperparathyroidism is a recognised, but rare, cause of acute pancreatitis. Hypercalcaemia caused by undiagnosed pHPT may be the only causative factor of recurrent acute pancreatitis. Patients and methods Three patients with multiple admissions for acute pancreatitis were diagnosed having pHPT during the work-up to identify possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, acute pancreatitis as the first clinical presentation in PHPT is rare. Hypercalcemia caused by undiagnosed PHPT may be the only causative factor in acute pancreatitis[8]. Therefore, this disease is often misdiagnosed or overlooked completely during clinical consultation.…”
Section: Introductionmentioning
confidence: 99%
“…However, acute pancreatitis as the first clinical presentation in PHPT is rare. Hypercalcemia caused by undiagnosed PHPT may be the only causative factor in acute pancreatitis[8]. Therefore, this disease is often misdiagnosed or overlooked completely during clinical consultation.…”
Section: Introductionmentioning
confidence: 99%
“…In this case decreased bone density and two pathologic fractures in the neck of the right femur and in the radius and ulna of the right hand were obvious on the first visit. We should remember that several types of malignancies present in the lung, head and neck, esophagus, breast, and renal cells, can cause paraneoplastic hypercalcemia and mimic signs and symptoms of parathyroid adenoma [ 15 ]. In the last 30 years the most contemporary series show an incidence of 20% or less.…”
Section: Discussionmentioning
confidence: 99%
“…The first report of primary hyperparathyroidism associated with pancreatic lithiasis was published in 1947. [8,9] From data collected between 1950 and 1975 it was found that of 1153 patients with primary hyperparathyroidism, only 17 patients (1.5%) had pancreatitis, and alternative causes for pancreatitis could be described. in some patients.29 The prevalence of acute pancreatitis in primary hyperparathyroidism is estimated to be between 1.5 -7%.…”
Section: International Journal Of Scientific Advancesmentioning
confidence: 99%